Venture Capital Policy Review Portugal - Tejada, Ricardo (OECD Science, Technology and Industry Working Papers, 2003)
The small Portuguese venture capital market is characterised by expansion-stage investments in manufacturing industries, primarily consumer goods. Government equity programmes, which have tended to be investment vehicles for European structural funds, have crowded out potential private investors. Recent initiatives, including a new venture captial law and a scheme aimed at leveraging private venture funding, should help stimulate venture activity. Measures are also needed to foster the emergence of more entrepreneurs, create a less risk-averse investment culture, and take fuller advantage of international venture capital flows. This paper analyses trends in Portuguese venture capital markets and makes policy recommendations which have been developed through an OECD peer review process ...